Dynamics in the Development of the Education System for Children with Autism Spectrum Disorders in Russia: Results of the 2021 National Monitoring - A.V. Khaustov; M.A. Schumskih (Moscow State University of Psychology and Education, 2022)
The results of the national monitoring of the education system of students with autism spectrum disorders (ASD), conducted in 2021 by the Ministry of Education of the Russian Federation in the cooperation with the Federal Resource Center for Organization of Comprehensive Support to Children with Autism Spectrum Disorders (FRC of MSUPE), are presented. The total amount of students with ASD in 2021 increased by 18% compared to 2020 and amounted to 39,117 individuals. The majority of children with ASD (71%) study at the levels of primary, basic and secondary general education. A much smaller proportion of ASD development at risk children is covered by early intervention - 1.5% of total number. The minimum number of adolescents and adults with ASD are included in the system of secondary vocational and higher education: 1.1% and 0.033%, respectively, of the total number of individuals with ASD in Russia. Monitoring revealed difficulties in the including children with ASD in the system of inclusive education. The proportion of students with ASD included in the inclusive educational model «Resource Class» is 7.5%. Homeschooled students with ASD make up 36% of the total number of students with autism. However, there is a positive trend in the availability of specialists for students with ASD: 98% of students with ASD receive psychological support; 74% - speech therapy; 66% - special teachers support; 70%f - social care teacher; tutor support - 33%. Tutor support remains the most urgent problem. In 52 subjects of the Russian Federation, 60 regional resource centers have been created, which require consulting and methodological support from the FRC of MSUPE.